CONGENITAL HYPOTHYROIDISM IN NEWBORN AND ASSOCIATION WITH SOCIODEMOGRAPHIC PARAMETERS AMONG NEONATE DELIVERED AT MILITARY HOSPITAL IN A CITY OF CENTRAL INDIA - ANISHA BEEGUM; SRUTI KRITI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The present study aims to assess the incidence of congenital hypothyroidism (CH) among neonates in a tertiary care hospital in central India, examining its association with various sociodemographic parameters. Methods: This cross-sectional study, conducted between January and December 2022, included all live births at a tertiary care center in Jabalpur, Madhya Pradesh. Cord blood thyroid-stimulating hormone (TSH) levels were measured for all newborns as part of routine screening. Sociodemographic data, including maternal age, gestational age, birth order, and newborn sex, were collected. Universal sampling was employed, encompassing all consenting parents and their neonates. Results: Among 388 live births, TSH values ranged from 0.23 to 35.59 mIU/L, with a mean TSH of 8.76±5.92 mIU/L. Of the neonates, 95.9% had normal TSH levels, while 4.1% exhibited elevated levels. Subsequent follow-up identified CH in two neonates (5.2 per thousand live births). Analysis revealed no significant association between elevated TSH levels and maternal age or newborn sex. However, a significant association was observed with gestational age. Birth order also displayed significance, with the third birth order having a higher proportion of neonates with raised TSH levels. Conclusion: This study highlights the importance of CH screening in preventing long-term complications and the various sociodemographic factors linked to CH, such as maternal age, gestational age, and birth order.